Identification and Evaluation of the Aerobic Capacity of Athletic and Rowing Team Players of Islamabad City (The Capital of Pakistan) - Muhammad Safdar Ali; Pro.Dr. Mohibullaha Khan Marwat; Ghulam Shabbir Anjum (The Sky, 2020)
Aerobic capacity is dominant factor of every individual for attaining dominating performance in sports particularly to achieve optimum performance in the endurance sports. The aim of study was to assess the aerobic capacity of the players of Athletics and rowing team of Islamabad. Aerobic and anaerobic exercises can be beneficial for the fitness and depending on the intensity, duration and events.  The mechanism of respiration and heart rate is differ in aerobic and anaerobic activities. Thirty athletes from middle and long distance events of track and field age group (23.9 ± 3.0) weight (64.13 ± 7.0) and thirty players of the rowing team age group (27.9 ± 4.1) weight (81.4 ± 8.7) from the Capital city Islamabad team were selected to investigate their aerobic capacity through the PACER (Progressive Aerobic Cardiovascular Endurance Run) test. The PACER